Failure Effects Evaluation for ATC Automation System. (2nd May 2017) - Li, Rui; Zhou, Zili; Cheng, Yansong; Wang, Jianqiang
Abstract : ATC (air traffic control) automation system is a complex system, which helps maintain the air traffic order, guarantee the flight interval, and prevent aircraft collision. It is essential to ensure the safety of air traffic. Failure effects evaluation is an important part of ATC automation system reliability engineering. The failure effects evaluation of ATC automation system is aimed at the effects of modules or components which affect the performance and functionality of the system. By analyzing and evaluating the failure modes and their causes and effects, some reasonable improvement measures and preventive maintenance plans can be established. In this paper, the failure effects evaluation framework considering performance and functionality of the system is established on the basis of reliability theory. Some algorithms for the quantitative evaluation of failure effects on performance of ATC automation system are proposed. According to the algorithms, the quantitative evaluation of reliability, availability, maintainability, and other assessment indicators can be calculated.